2004
DOI: 10.1002/tcr.20007
|View full text |Cite
|
Sign up to set email alerts
|

Tunable haptotropic metal migration in fused arenes: towards organometallic switches

Abstract: Tricarbonyl chromium complexes of naphthalene derivatives are synthesized by chromium-templated [3 + 2 + 1]-benzannulation and subjected to thermally induced haptotropic rearrangement experiments. Thermodynamic and kinetic parameters for the metal shift demonstrate the influence of the arene substitution pattern. In turn, the chromium template may be tuned as well by phosphorus coligands which allow to accelerate or slow down the isomerization process; this effect quantitatively reflects the steric and electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 34 publications
0
30
0
2
Order By: Relevance
“…Up to three Ru(cyclopentadienyl) fragments were found to be η 6 ‐coordinated to alternating phenylenes in [6]CPP , and DFT calculations shed light on the observed regioselectivity. An interesting question that remains open is whether the organometallic complexes are fluxional in solution, that is, whether the metallic motives are “walking” along the rings, as has been demonstrated in related planar systems …”
Section: Metal Coordinationmentioning
confidence: 99%
“…Up to three Ru(cyclopentadienyl) fragments were found to be η 6 ‐coordinated to alternating phenylenes in [6]CPP , and DFT calculations shed light on the observed regioselectivity. An interesting question that remains open is whether the organometallic complexes are fluxional in solution, that is, whether the metallic motives are “walking” along the rings, as has been demonstrated in related planar systems …”
Section: Metal Coordinationmentioning
confidence: 99%
“…Dçtz and Jahr suggested that these haptotropic migrations can be used as novel organometallic molecular switches [72] in which this rearrangement can be tuned by modification of the reaction conditions or by photoinduction of these chemical species. They also reviewed a variety of benzannulation reactions where this haptotropic migration plays an important role in the synthesis and regioselectivity of organic compounds.…”
mentioning
confidence: 99%
“…Bis zu drei Ru(cyclopentadienyl)‐Fragmente mit η 6 ‐Koordination wurden auf alternierenden Phenylenen im [6]CPP gefunden, und ihre Regioselektivität wurde mittels DFT‐Rechnungen aufgeklärt. Eine interessante, aber offene Frage bleibt, ob die metallorganischen Komplexe in Lösung beweglich sind, d. h., ob die metallischen Bausteine entlang der Ringe wandern, wie es in verwandten Planarsystemen gezeigt wurde …”
Section: Koordination An Metalleunclassified